The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s12117-019-09366-7
|View full text |Cite
|
Sign up to set email alerts
|

Criminal networks in a digitised world: on the nexus of borderless opportunities and local embeddedness

Abstract: This article presents the results of empirical analyses of the use of information technology (IT) by organized crime groups. In particular, it explores how the use of IT affects the processes of origin and growth of criminal networks. The empirical data presented in this article consist of 30 large scale criminal investigations into organized crime, including traditional organized crime, traditional organized crime in which IT is an innovative element, low tech cybercrimes and high tech cybercrimes. Networks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Empirical research into organized cybercrime in the Netherlands, Germany, England, Sweden, and the United States shows that the structure of a number of cybercriminal networks is similar to that of traditional networks (Bulanova-Hristova et al 2016;Werner and Korsell 2016;Leukfeldt et al 2017b, c, d;Odinot et al 2017;Kruisbergen et al 2018;Leukfeldt et al 2019). For example, most of the cybercriminal networks studied by these authors consisted of a more or less stable group of core members who committed offenses together for a prolonged period of time.…”
Section: Structure and Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical research into organized cybercrime in the Netherlands, Germany, England, Sweden, and the United States shows that the structure of a number of cybercriminal networks is similar to that of traditional networks (Bulanova-Hristova et al 2016;Werner and Korsell 2016;Leukfeldt et al 2017b, c, d;Odinot et al 2017;Kruisbergen et al 2018;Leukfeldt et al 2019). For example, most of the cybercriminal networks studied by these authors consisted of a more or less stable group of core members who committed offenses together for a prolonged period of time.…”
Section: Structure and Compositionmentioning
confidence: 99%
“…Furthermore, several studies on cybercriminal networks illustrate, similar to traditional networks, the importance of actors functioning as brokers (Soudijn and Monsma 2012;Lu et al 2010;Yip et al 2012;Holt and Smirnova 2014;Décary-Hétu and Dupont 2012;Leukfeldt et al 2017cLeukfeldt et al , e, 2019. Traditionally, so-called brokers were needed to overcome the limitations of offline social networks.…”
Section: Structure and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along the same area of research other studies explored the organizational structures of groups involved in cybercrime [34]- [37]. For instance, Leukfeldt et al [36] discuss the differences distinguished between networks carrying out lowtech attacks and high-tech attacks as well as the different layers of these networks such as the core members (the higher lever), professional enablers (a layer below the core members) and money mules (the bottom layer).…”
Section: F Primary Research Contributions In the Fieldmentioning
confidence: 99%
“…It is also identified that researchers are selecting some parts of specific frameworks which they find appropriate to analyse the type of data they have collected or analysing. For example, a study [34] has selected some aspects of an analytical framework [30] used to systematically analyse cases of organised crime. The selected aspects of the framework were ties between members of networks, processes of origin and growth, the composition of the network, its structure, the dependencies, the background of members, social ties and the (digital) offender convergence settings used by the criminals.…”
Section: Approaches To Profiling or Understanding Cybercriminalsmentioning
confidence: 99%